Clinical, biochemical, neuroradiological and molecular characterization of Egyptian patients with glutaric acidemia type 1 - Hatem Zayed (835448) (2019)
Glutaric acidemia type 1 (GA1) is an inherited metabolic autosomal recessive disorder that is caused by a deficiency in glutaryl-CoA dehydrogenase (GCDH). Untreated patients suffer primarily from severe striatal damage. More than 250 variants in the GCDH gene have been reported with a variable frequency among different ethnic groups. In this study, we aimed to characterize 89 Egyptian patients with GA1 and identify the variants in the 41 patients who were available for genotyping. All of our patients demonstrated clinical, neuroradiological, and biochemical characteristics that are consistent with a diagnosis of GA1. All patients presented with variable degrees of developmental delay ranging from mild to severe. Most of the 89 patients presented with acute onset type (71.9%), followed by insidious (19%) and asymptomatic (9%). A delay in diagnosis was inversely associated with macrocephaly. The prevalence rate ratio (PR) for macrocephaly that was associated with each 6-month delay was 0.95 (95%CI 0.91–0.99). However, high body weight was associated with a higher likelihood of having macrocephaly (PR 1.16, 95%CI 1.06–1.26 per 1 SD increment of Z score weight). However, body weight was inversely associated with the morbidity score. Consanguinity level was 64% among our patient’s cohort and was positively associated with the C5DC level (β (95%CI) 1.06 (0.12–1.99)). Forty-one patients were available for genotyping and were sequenced for the GCDH gene. We identified a total of 25 variants, of which the following six novel variants were identified: three missense variants, c.320G > T (p.Gly107Val), c.481C > T (p.Arg161Trp) and c.572 T > G (p.Met191Arg); two deletions, c.78delG (p.Ala27Argfs34) and c.1035delG (p.Gly346Alafs*11); and one indel, c.272_331del (p.Val91_Lys111delinsGlu). All of the novel variants were absent in the 300 normal chromosomes. The most common variant, c.*165A > G, was detected in 42 alleles, and the most commonly detected missense variant, c.1204C > T (p.Arg402Trp), was identified in 29 mutated alleles in 15/41 (34.2%) of patients. Our findings suggest that GA1 is not uncommon organic acidemia disease in Egypt; therefore, there is a need for supporting neonatal screening programs in Egypt. Other Information Published in: Metabolic Brain Disease License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s11011-019-00422-3